Mechanical Modification of Resin Capsules by Adding Steel Particles - Xiaowei Feng; Fei Xue; Tongyang Zhao; Wenjie Jiang (Shock and Vibration)
Five kinds of steel particles with sizes ranging from 0.6 mm to 2.2 mm with increments of 0.4 mm were mixed with mining resin materials, and the mixing ratio of the particles was also varied. By using this approach, the film gloving problem of coal mine bolting should be effectively solved due to the shredding effects of the particles during bolt rotation. The premise is that the mechanical behavior should not be weakened under such conditions. A total of 47 standard cylindrical specimens were manually prepared, which included pure resin specimens and specimens containing particles with different sizes and weights. First, the homogeneity of a prepared standard specimen was verified by computed tomography (CT) scanning technology. Second, the mechanical improvements provided by each type of particle were evaluated. Thirdly, the effectiveness of both the particle weight and particle size was comprehensively discussed, and the eventual recommendation was to set for the particle size and weight as 1.4 mm and 40 g, respectively, and the particles weight percentage was 7.27%. Finally, the failure patterns for all specimens were collected and comprehensively compared. Additionally, pullout tests were carried out to vindicate the recommended particle size and weight.